2021
DOI: 10.5267/j.msl.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of entrepreneurship quality education in higher educational institutions: A mediating effect of entrepreneurial training

Abstract: The main aim of this study is to assess the effectiveness of entrepreneurship quality education in higher education institutions in Indonesia on entrepreneurial goal intentions with the mediating effect of entrepreneurial training. The research followed the quantitative research design as the researcher collected data based on numeric facts. The sample size was 314 participants and a test was carried out on Smart PLS. The results were based on the measurement model to test the factor loadings, validity and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The existence of Eduperneurship in higher education shows that there is quality in the field of entrepreneurship education (Raza et al, 2021). With this case study, we see that universities to achieve 21st century education are one of them with applied entrepreneurship education.…”
Section: Pdca-based Edupreneurs Through Activities Outside Of Collegementioning
confidence: 72%
“…The existence of Eduperneurship in higher education shows that there is quality in the field of entrepreneurship education (Raza et al, 2021). With this case study, we see that universities to achieve 21st century education are one of them with applied entrepreneurship education.…”
Section: Pdca-based Edupreneurs Through Activities Outside Of Collegementioning
confidence: 72%
“…Mu et al ( 2020 ) showed that in the evaluation of their temper and character, the number of students who choose good, general, very good, poor, and very poor is 63, 52, 35, 16, and 13, respectively. Raza et al ( 2021 ) indicated that the vast majority of college students think that they have an ordinary or better temper and character, and only a few of the students think that their temper and character are very bad.…”
Section: Research Results and Analysismentioning
confidence: 99%
“…The landscape of engineering education has transformed, with numerous institutions integrating technology and modern learning labs into their curricula (Jain, 2018). Within higher education, the quality of entrepreneurship education is shaped by entrepreneurial training, influencing entrepreneurial orientation (Jiang et al, 2017;Raza et al, 2021). Despite the presence of Entrepreneurship Development Cells and various activities in academic institutes, the outcomes have not yielded constructive results (Prabhu, 2020;Sao & Balpande, 2018).…”
Section: Engineering Disciplinesmentioning
confidence: 99%